Eksistensi Media Sosial,Youtube, Instagram dan Whatsapp Ditengah Pandemi Covid-19 Dikalangan Masyarakat Virtual Indonesia - Junawan, Hendra; Laugu, Nurdin (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Introduction. This article discusses the existence of social media YouTube, Instagram and Watsapp in the midst of the Covid-19 pandemic among virtual communities in Indonesia. The development of social media is increasing every year, especially in the conditions of the corona virus outbreak. The development of social media in Indonesia has experienced a very significant increase, it can be seen that Indonesia is in the 3rd position of social media users in the world. Data Collection Method. The method used in this article is by using the literature method by reading literature related to discussion and it can be analyzed that the existence of social media such as YouTube in the midst of the Covid pandemic has experienced a surge in users of around 88% and is then followed by Whatsapp social media with the number of accesses of 84% and Instagram with 79%. Results and Discussions. Based on the data above, we can see the development and level of existence of several social media which is frequently accessed by the world's population during the Covid 19 pandemic. This development has certainly experienced a very clear penetration of internet users among the Indonesian virtual community. Conclusions. the development of social media in Indonesia and globally has increased very significantly. The existence of social media which was popular during the Covid-19 pandemic, which placed YouTube as the first media that was very popular with the highest number of users in the world.